Metastatic Renal Cell Carcinoma with Level IV Thrombus: Contemporary Management with Complete Response to Neoadjuvant Targeted Therapy. (14th March 2019) - Bhat, Abhishek; Nahar, Bruno; Venkatramani, Vivek; Banerjee, Indraneel; Kryvenko, Oleksandr N.; Parekh, Dipen J.
Abstract : Renal cell carcinoma, particularly the most common clear cell type, is one of the most aggressive of urological cancers with significant risk of metastatic spread. It also has a propensity for venotropism with a proportion of tumors developing thrombi up to the right atrium. The response with newly adopted targeted therapy has been considered to be in the evolutionary stage with no clear role with respect to debulking or reducing the size of the inferior vena cava (IVC) thrombus. We describe a case of a right-sided metastatic RCC with Level IV thrombus initially managed with Pazopanib followed by Nivolumab and Adalimumab followed by cytoreductive nephrectomy and IVC thrombectomy in the post-targeted therapy setting with complete curative response.